2018
DOI: 10.1007/s11442-018-1495-8
|View full text |Cite
|
Sign up to set email alerts
|

Immediately downstream effects of Three Gorges Dam on channel sandbars morphodynamics between Yichang-Chenglingji Reach of the Changjiang River, China

Abstract: Sandbars are of vital ecological and environmental significance, which however, have been intensively influenced by human activities. Morphodynamic processes of sandbars along the Yichang-Chenglingji Reach of the Changjiang River, the channel immediately downstream of the Three Gorges Dam (TGD), are assessed based on remote sensing images between 2000 and 2016. It can be found that the entire area of sandbars reduces drastically by 19.23% from 149.04 km 2 in 2003 to 120.38 km 2 in 2016, accompanied with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 64 publications
(83 reference statements)
0
33
1
Order By: Relevance
“…These results imply that the larger the size of MCB, the greater relative stability in area and shape variations, whereas the smaller size of the MCBs, the less stable in terms of area and shape variations. In previous studies, only one specific scale MCBs were focused (such as large-size MCBs), and the temporal dynamic patterns of other sizes of MCBs were not addressed [23,30].…”
Section: Scale Effects On the Temporal Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results imply that the larger the size of MCB, the greater relative stability in area and shape variations, whereas the smaller size of the MCBs, the less stable in terms of area and shape variations. In previous studies, only one specific scale MCBs were focused (such as large-size MCBs), and the temporal dynamic patterns of other sizes of MCBs were not addressed [23,30].…”
Section: Scale Effects On the Temporal Dynamicsmentioning
confidence: 99%
“…As an essential geomorphic unit and component in a fluvial system, 3 of 21 channel morphology dynamics [17,35,36]. However, only a few studies analyzed the MCB dynamics at a large spatiotemporal scale with the help of RS technology [12,23,30,37]. For example, in the reach immediately downstream of TGD, Wang et al [23] found that the total area of MCBs extracted from Landsat images reduced dramatically by 19.23% from 2003 to 2016, accompanied with an increase of water surface width.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large amounts of riverine water and SSD are discharged in the funnel‐shaped estuary during the monsoon season, developing bifurcations with migrating channels and tidal bars. Some studies indicate that the fluvial SSD input has decreased by 70% after the construction of the Three Gorges Dam (TGD) in 2003, triggering local erosion in the offshore area of the Changjiang Delta (Dai et al, 2016; Wang et al, 2018). Recent studies suggest that sediment supplied from the ocean can alleviate the current estuarine erosion, providing material to tidal flats and shoals (Dai et al, 2013, 2018; Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Capolongo et al coupled multitemporal remote sensing with geomorphology and hydrological modelling for post-flood recovery in the Strymonas dammed river basin [12]. There also have been many studies on the morphodynamic processes of sandbars in the Yangtze River, the channel downstream of the Three Gorges Dam (TGD) in China [13][14][15][16][17][18]. The decreased sediment load in the middle of the Yangtze River was found to be responsible for dramatic changes of channel bar morphodynamics, which could last for a long time, depending on the operation of the Three Gorges Dam in 2003 [19].…”
Section: Introductionmentioning
confidence: 99%